Localized state exciton model investigation of B-content effect on optical properties of BGaAs/GaAs epilayers grown by MOCVD. (October 2016) - Hidouri, T.; Saidi, F.; Maaref, H.; Rodriguez, Ph.; Auvray, L.
Abstract: In this work, Bx Ga1−x As/GaAs epilayers with three different boron compositions were elaborated by Metal Organic Chemical Vapor Deposition (MOCVD) on GaAs (001) substrate. The boron fraction has been estimated using High resolution X-ray diffraction (HRXRD) spectroscopy. Using the photoluminescence PL spectroscopy, the emission energy as well as the PL intensity was carried out as functions of temperature in the range 10–300 K. The temperature dependence of the PL peak energy has shown an S -shaped behavior. It is a result of the competition process between localized and delocalized states induced by the boron clusters. We have shown that the localization effects increase by increasing boron composition and then drops for high compositions (up to 8%). Qualitative and quantitative interpretations based on the Localized States Exciton (LSE) parameters evolution in order to explain the unusual photoluminescence behavior of the two luminescence keys. At high temperatures, the model can be approximated to the band-tail-state emission. The LSE model succeeds in accurately reproducing of the atypical PL peak emission and normalized intensity of BGaAs/GaAs epilayers. Highlights: We report the effect of temperature on the optical properties of BGaAs/GaAs epilayers. Abnormal behavior of the luminescence keys has been observed. LSE model was used to fit the S -shaped behavior and normalized PL intensity. Novel qualitative and quantitative re-interpretations based on the LSE model were investigated.